Honesty toward the Holy Day - Ronen Bar-El; Yossi Tobol (Institute of Labor Economics (IZA), 2017)
We study the effect of religiosity, gender, and "day of the week", on the level of honesty by conducting under-the-cup experiment among religious and secular, female and male Jewish students. We show that the level of honesty among religious subject, males and females, increases as the day of the experiment is closer to the upcoming Saturday, the Jewish holy day. We also found that the "Saturday effect" does not exist among secular subjects. In addition, we found that the religious females show the highest level of honesty, especially on Thursday. Finally, we derive practical implication from our study.
Keywords: C91; D63; Z12; 330; gender effect; holy day effect; honesty; religiosity